Illuminating IntCal during the younger dryas - Reinig, Frederick; Sookdeo, Adam; Esper, Jan; Friedrich, Michael; Guidobaldi, Giulia; Helle, Gerhard; Kromer, Bernd; Nievergelt, Daniel; Pauly, Maren; Tegel, Willy; Treydte, Kerstin; Wacker, Lukas; et al. (Radiocarbon, 2020)
As the worldwide standard for radiocarbon (14C) dating over the past ca. 50,000 years, the International Calibration Curve (IntCal) is continuously improving towards higher resolution and replication. Tree-ring-based 14C measurements provide absolute dating throughout most of the Holocene, although high-precision data are limited for the Younger Dryas interval and farther back in time. Here, we describe the dendrochronological characteristics of 1448 new 14C dates, between ~11,950 and 13,160 cal BP, from 13 pines that were growing in Switzerland. Significantly enhancing the ongoing IntCal update (IntCal20), this Late Glacial (LG) compilation contains more annually precise 14C dates than any other contribution during any other period of time. Thus, our results now provide unique geochronological dating into the Younger Dryas, a pivotal period of climate and environmental change at the transition from LG into Early Holocene conditions.